1971
DOI: 10.1079/bjn19710073
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the food intake of sheep at a single meal

Abstract: I . Experiments are described in which the food intake and the water intake of sheep at a single meal were measured. The sheep were offered lucerne chaff ad lib. for z h only each day. 2.Following the peritoneal infusion of physiological saline the food intake increased, while the injection of a diuretic before feeding caused the food intake to be decreased.3. In eight experiments the osmolality of the ruminal liquor was increased by the addition to the rumen of NaCl, KCl or the salts of volatile fatty acids i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…However, it can be said that most theories of satiety relate it primarily to the volume and physical and chemical composition of the food in the gut (Baile, 1968). The exception is that of Ternouth & Beattie (1971) who relate satiety in sheep, in part, to changes in plasma osmolarity consequent upon fluid shifts into the gut at feeding time.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be said that most theories of satiety relate it primarily to the volume and physical and chemical composition of the food in the gut (Baile, 1968). The exception is that of Ternouth & Beattie (1971) who relate satiety in sheep, in part, to changes in plasma osmolarity consequent upon fluid shifts into the gut at feeding time.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, intraruminal infusion of sodium acetate solutions depresses intake more than equimolar amounts of sodium chloride both in sheep 21 and in cows 22 . On the other hand, the effects of salt infusions into the rumen on feed intake are very much less when access to water is allowed, compared with when water is withheld 23,24 , and it is to be noted that Carter & Grovum 20 deprived their sheep of water during the infusion periods, thereby exacerbating the effects of the salts. It is deduced that the osmolality of rumen contents might be one factor influencing feed intake, but is not of over-riding importance.…”
Section: Metabolic Factorsmentioning
confidence: 99%
“…For a given level of energy infused, feed intake response is inversely proportional to the size of the molecule. Osmolarity in the rumen, however, seems to be a major satiation factor, as salt infusion studies have shown (Ternouth & Beattie, 1971;Bergen, 1972). This observation suggests that the VFA action cue may be of an osmotic nature.…”
Section: Energy Nutrientsmentioning
confidence: 99%